Modelo de regresión múltiple aplicado al proceso de admisión de la Universidad de Panamá - Cunningham, José (2007)
The University of Panama since the year 1993 uses in its process of admission, diagnostic tests such as the GATB, PCA and the PCG as variables to indicate and help predict academic success. The contributions made by each one of these variables to forecast the outcome is established using the multiple regression equation. The present work of this investigation includes a new variable that is added to the three already mentioned, it is using the grade point average achieved in High School. Historically, it has been considered as a good prognosticator in the academic field, but in this occasion it is used as a linear model to verify its real contribution to the prediction of the cumulative academic index of the second semester. An univariate descriptive analysis, and then a correlational analysis is made between all the variables of the study which also includes multiple intercorrelations and correlations; finally, the equation and coefficients to predict the prognosis for each academic area appear. The new findings reflected in the results of this investigation can help reframe the future use of these prognosticators and to help look for better alternatives in the process of admissions.